The Effect of Ethnoscience-Integrated Science Teaching Materials on Junior High School Students’ Scientific Literacy - Rizka Isnaeni; Mahrus Mahrus; Alauddin Shahih; Zaena Sultona Osi; Fana Tri Prihatini (Indonesian Journal of Educational Innovation, 2026)
Scientific literacy is an essential competency in twenty-first-century science education, yet Indonesian students’ achievement in this area remains relatively low. One possible contributing factor is the limited availability of contextual teaching materials that connect formal science concepts with students’ sociocultural environment. This study aimed to analyze the effect of ethnoscience-integrated science teaching materials on eighth-grade students’ scientific literacy at MTs. Birrul Walidaini NW Bertong. The study employed a quantitative pre-experimental method with a one-group pretest-posttest design involving 20 students selected through saturated sampling. Data were collected using a scientific literacy test and analyzed descriptively and inferentially through normalized gain (N-gain), the Shapiro-Wilk normality test, and a paired-sample t-test. The results showed a statistically significant increase in students’ scientific literacy (p < 0.05), with the mean score rising from 54.95 on the pretest to 78.60 on the posttest, and an average N-gain of 0.575, placing it in the medium category. These findings suggest that ethnoscience-integrated teaching materials are highly effective in improving scientific literacy, particularly when implemented through guided inquiry with adequate teacher scaffolding, by bridging abstract scientific concepts with students’ everyday cultural realities. The study provides empirical support for culturally responsive, context-based science learning and offers practical implications for the development of science teaching materials in madrasah settings.